Prognostic value of total number of lymph nodes retrieved differs between left-sided colon cancer and right-sided colon cancer in stage III patients with colon cancer - Yang, Lin (BMC Cancer, 2018)
BACKGROUND: The consensus is that a minimum of 12 lymph nodes should be analyzed at colectomy for colon cancer. However, right colon cancer and left colon cancer have different characteristics, and this threshold value for total number of lymph nodes retrieved may not be universally applicable. METHODS: The data of 63,243 patients with colon cancer treated between 2004 and 2012 were retrieved from the National Cancer Institute’s Surveillance, Epidemiology, and End Results database. Multivariate Cox regression analysis was used to determine the predictive value of total number of lymph nodes for survival after adjusting for lymph nodes ratio. The predictive value in left-sided colon cancer and right-sided colon cancer was compared. The optimal total number of lymph nodes cutoff value for prediction of overall survival was identified using the online tool Cutoff Finder. Survival of patients with high total number of lymph nodes (≥12) and low total number of lymph nodes (< 12) was compared by Kaplan–Meier analysis. RESULTS: After stratifying by lymph nodes ratio status, total number of lymph nodes≥12 remained an independent predictor of survival in the whole cohort and in right-sided colon cancer, but not in left-sided colon cancer. The optimal cutoff value for total number of lymph nodes was determined to be 11. Low total number of lymph nodes (< 11) was associated with significantly poorer survival after adjusting for lymph nodes ratio in all subgroups except in the subgroup with high lymph nodes ratio (0.5–1.0). CONCLUSIONS: Previous reports of the prognostic significance of total number of lymph nodes on node-positive colon cancer were confounded by lymph nodes ratio. The 12-node standard for total number of lymph nodes may not be equally applicable in right-sided colon cancer and left-sided colon cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4431-5) contains supplementary material, which is available to authorized users.